A KEADILAN DISTRIBUSI DAN PERLINDUNGAN TERHADAP KAUM LEMAH - Rodiah, Siti; Hamid, Abdul (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2025)
Distributional justice and protection of the weak are two important issues in efforts to create a just and prosperous society. Distributive justice includes the principle that resources, wealth, and opportunities must be distributed equally so that every individual, especially those in vulnerable positions, has equal access. This concept is strengthened by the justice theory of John Rawls and Aristotle, which emphasizes the importance of social policies that support the welfare of weak groups. In the Indonesian context, significant social and economic inequality demands serious attention, especially in the form of inclusive policies and legal support. In addition, the Islamic perspective provides an additional dimension in understanding distributional justice through the mechanisms of zakat, infaq and alms, which function to prevent the accumulation of wealth in the hands of a few people. With collaboration between the government, civil society and the private sector, it is hoped that efforts to achieve distributional justice and protect the weak can be realized effectively. This paper aims to analyze the concept of distributive justice, identify the challenges faced by the weak, and encourage social awareness regarding the importance of justice and protection for vulnerable groups.